2022
DOI: 10.3390/polym14061230
|View full text |Cite
|
Sign up to set email alerts
|

Shape-Memory Composites Based on Ionic Elastomers

Abstract: Shape-memory polymers tend to present rigid behavior at ambient temperature, being unable to deform in this state. To obtain soft shape-memory elastomers, composites based on a commercial rubber crosslinked by both ionic and covalent bonds were developed, as these materials do not lose their elastomeric behavior below their transition (or activation) temperature (using ionic transition for such a purpose). The introduction of fillers, such as carbon black and multiwalled carbon nanotubes (MWCNTs), was studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 75 publications
(82 reference statements)
0
6
0
Order By: Relevance
“… 39 The same work showed that the 2W-SM effect of the composite was lost when the concentration of CB was increased to 20 vol %. At the required high concentrations for resistive heating at moderate voltages (>15 wt %), this family of SMCs was reported to have lower recovery ratios, 85 more brittle behavior leading to failure of the material at shorter deformations, 86 , 87 and, in some cases, severely worsened shape fixity. 88 The last effect is found in semicrystalline SMP composites, since the addition of CBs decreases the amount of crystalline regions within the composite, 39 which are in charge of fixing the temporary shape.…”
Section: Electro- and Magnetoactive Smcs: Fillers And Activationmentioning
confidence: 99%
See 2 more Smart Citations
“… 39 The same work showed that the 2W-SM effect of the composite was lost when the concentration of CB was increased to 20 vol %. At the required high concentrations for resistive heating at moderate voltages (>15 wt %), this family of SMCs was reported to have lower recovery ratios, 85 more brittle behavior leading to failure of the material at shorter deformations, 86 , 87 and, in some cases, severely worsened shape fixity. 88 The last effect is found in semicrystalline SMP composites, since the addition of CBs decreases the amount of crystalline regions within the composite, 39 which are in charge of fixing the temporary shape.…”
Section: Electro- and Magnetoactive Smcs: Fillers And Activationmentioning
confidence: 99%
“…It also has been shown that, at the same concentrations, CNT-filled SMCs exhibit higher shape fixity than other fillers, such as CBs, 87 which may be attributed to the alignment of the CNTs in the direction of the deformation. In the same work, the authors also showed that their shape memory elastomer filled with CNTs displays a better shape recovery ratio and better overall shape memory characteristics, as can be seen in Figure 4 .…”
Section: Electro- and Magnetoactive Smcs: Fillers And Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…A category of smart materials, SMEs react to external stimuli such as temperature, pressure, electromagnetic fields, chemicals (and pH), water, light, and so on. The responsive physical properties could be stiffness, shape, and damping, among others [1,9,14,24,[40][41][42]. A recent SME was developed by Rim et al (2022) [43].…”
Section: Polymermentioning
confidence: 99%
“…Smart materials can acquire, convey, or process a stimulus and reply by creating a 'useful' effect. This ability offers opportunities for responsive materials in applications such as actuation, shape memory, and sensing in industries including biomedicine, aerospace, textiles, and so on [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%